(untitled) (Orthodontic Journal of Nepal, 2018)
Introduction: Standardized cephalogram is used for the orthodontic diagnosis and treatment planning and the measured values of the craniofacial structures are compared with the peer group having similar age, gender and ethnicity. However, this standardized comparison has not been possible so far for Newar ethnic group. Objective: To determine cephalometric norms of Newar adults of Kathmandu using McNamara analysis and to assess gender difference within the group. Materials & Method: Newar Indo-Aryan descendents aged 18-27 years were screened based on inclusion criteria. Lateral cephalometric radiographs of 62 untreated Newar adults (20 males and 42 females) were used. Manual tracing of the lateral cephalograms were performed and descriptive statistics were obtained. Comparative test was conducted within Newars to evaluate gender diversity at the significance level p≤0.05. Result: Craniofacial structures of male and female Newars were significantly different. Parameters showing these differences were Effective Mid Face Length, Effective Mandibular Length, Lower Anterior Facial Height. Conclusion: Standardized comparison with the peer group separately for male and female should be done when analysing cephalometry for any ethnic group.